Controlling current and voltage type interfaces in power‐hardware‐in‐the‐loop simulations. Issue 10 (1st October 2014) - Dargahi, Mahdi; Ghosh, Arindam; Davari, Pooya; Ledwich, Gerard
Abstract : The usual practice to study a large power system is through digital computer simulation. However, the impact of large scale use of small distributed generators on a power network cannot be evaluated strictly by simulation since many of these components cannot be accurately modelled. Moreover, the network complexity makes the task of practical testing on a physical network nearly impossible. This study discusses the paradigm of interfacing a real‐time simulation of a power system to real‐life hardware devices. This type of splitting a network into two parts and running a real‐time simulation with a physical system in parallel is usually termed as power‐hardware‐in‐the‐loop (PHIL) simulation. The hardware part is driven by a voltage source converter that amplifies the signals of the simulator. In this paper, the effects of suitable control strategy on the performance of PHIL and the associated stability aspects are analysed in detail. The analyses are validated through several experimental tests using an real‐time digital simulator.